Enhanced viability and stability of the Lactobacillus reuteri DSM 17938 probiotic strain following microencapsulation in pea and rice protein-inulin conjugates - Mudgil, Priti; Alkaabi, Fatima; Khan, Hina; Javed, Miral; Hajamohideen, Abdul Razack; Hamed, Fatallah; Maqsood, Sajid (Frontiers in Sustainable Food Systems, 2024)
Probiotics, which offer various health benefits can face challenges in terms of stability during food processing, storage, and gastrointestinal digestion. Therefore, this study aimed to improve the stability and survival of probiotics during various processing conditions and storage. To address this issue, the study was designed to microencapsulate Lactobacillus reuteri DSM 17938 within plant proteins (specifically rice protein (RP) and pea protein (PeP)) and their Maillard reaction conjugated with inulin by spray-drying. The encapsulation efficiency (EE%), stability during storage and temperature, and the viability after simulated gastrointestinal digestion of the microcapsules were examined. The results demonstrate that individual proteins exhibited lower EE%; however, the Maillard conjugates showed increased EE%, with RC (rice protein conjugates) displaying a higher EE% (96.99%) than PC (pea protein conjugates) (92.87%) (p < 0.05). Fourier Transform Infrared Spectroscopy verified the interaction between different functional groups of the proteins and Maillard conjugated and indicated the successful encapsulation of Lactobacillus reuteri DSM 17938 cells. The results also suggested that RC-encapsulated probiotic cells exhibited maximum survival upon gastrointestinal transit, with a decline of only 1.24 and 1.52 log CFU/g after gastric and complete simulated gastrointestinal digestion, respectively. The viability of probiotics encapsulated with RC and PeC showed improvement compared to those encapsulated with RP and PeP, particularly during refrigerated and room temperature storage, thermal challenge, and simulated gastrointestinal transit. Overall, these findings suggest that plant proteins and prebiotic inulin conjugates could serve as promising new encapsulation matrices for the encapsulation of probiotics in food applications.